Different Mutations of Gap Junction Connexin 47 Lead to Discrepant Activation of Unfolded Protein Response Pathway in Pelizaeus–Merzbacher-Like Disease - Chen, Na; Wang, Jingmin; Jiang, Yuwu; Wu, Ye; Hao, Hongjun; Ji, Taoyun (Neuropediatrics, 2017)
Background The unfolded protein response (UPR) includes three cascade pathways, which are responsible for the elimination of overload protein that is accumulated in the endoplasmic reticulum (ER). We hypothesize that mutations in connexin 47 (Cx47) lead to abnormal retain of the protein in the ER lumen, which causes Pelizaeus–Merzbacher-like disease (PMLD), a hypomyelinating leukodystrophic disorder.Methods In this study, the influence of mutant Cx47 on the three UPR cascade pathways and discrepant UPR activation was analyzed in an oligodendrocyte cell line transfected with different mutations in the first extracellular loop of Cx47. As over activated UPR pathway would lead to cell apoptosis, cell viability and apoptosis were also compared between the different mutants.Results The elevated UPR level accompanied with higher apoptotic rates were measured in the c.138C > G or c.217C > T-transduced oligodendrocytes, but not in the c.216delGinsAA group, compared with the wild-type and empty vector groups. Cell viability was lower in oligodendrocytes transfected with the mutation of c.138C > G or c.217C > T, but not in the c.216delGinsAA group.Conclusion Different mutations in the Cx47 lead to discrepant activation of UPR pathway, which encouraged apoptotic cell death at different levels. Inappropriate activation of UPR may play important roles in the pathophysiology of PMLD.
Keywords: Pelizaeus–Merzbacher-like disease; connexin 47; unfolded protein response; apoptosis